Comparative evaluation of the effects of atorvastatin and lovastatin on the pharmacokinetics of aliskiren in rats - Sharaf, Amal; El-Shazly, Kamal A.; Abd El Latif, Amera; Abdelkawy, Khaled S.; Elbarbry, Fawzy; Khalifa, Hazim O. (Penerbit Universiti Kebangsaan Malaysia, 2021)
The worldwide increase in the number patients with high blood pressure poses serious clinical challenges. Little is known regarding the interactions between the various drugs used to treat heart diseases. The present study evaluates and compares the effects of administration of multiple doses of atorvastatin or lovastatin on the pharmacokinetics of aliskiren in rats in an effort to determine their underlying mechanisms. A total of 90 healthy female albino rats were randomly divided into three groups. All groups were treated with aliskiren by oral gavage at 8.57 mg/kg daily for 14 days. In addition to aliskiren, group 2 received atorvastatin at a dose of 1.143 mg/kg for 7 days. In addition to aliskiren, group 3 received lovastatin at a dose of 1.143 mg/kg for 7 days. After blood samples were collected at specific time intervals, aliskiren concentrations were determined using liquid chromatography-tandem mass spectrometry. Relative to the control treatment, atorvastatin treatment resulted in non-significant alterations in the pharmacokinetic parameters of aliskiren. In contrast, lovastatin resulted in a significant increase in the area under the curve, peak plasma concentration, and elimination half-life by 21, 10, and 72%, respectively. Additionally, lovastatin significantly reduced oral clearance by 23%. Inhibition of aliskiren metabolism via the hepatic CYP3A subfamily and/or inhibition of intestinal P-glycoprotein and/or the CYP3A subfamily was identified as a possible mechanism. This study is the first to report that only lovastatin causes a marked increase in aliskiren bioavailability. Caution should be taken when lovastatin and aliskiren are administrated concomitantly in clinical practice.